2015
DOI: 10.3892/mco.2015.574
|View full text |Cite
|
Sign up to set email alerts
|

High vascular endothelial growth factor gene expression predicts poor outcome in patients with non-luminal A breast cancer

Abstract: Breast cancer is the most frequent type of cancer among women worldwide. Vascular endothelial growth factor (VEGF), the key modulator of angiogenesis, has been implicated in breast cancer susceptibility and aggressiveness. expression was determined in 99 breast cancer tissue samples using reverse transcription-polymerase chain reaction and the human epidermal growth factor receptor 2 (HER2) status was determined by immunohistochemistry. Subsequently, the associations of, HER2 and hormone receptor status with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…In our study, conducted in the pre-trastuzumab era, we found that high VEGF-A, VEGF-C, VEGFR2 and VEGFR3 protein expression was associated with certain adverse prognostic factors, such as ER/PgR-negative and/or HER2-positive status, suggesting that high protein expression of VEGF family members might have a negative prognostic impact on DFS or OS. Our findings are consistent with the results of recent studies[ 19 , 29 , 30 ] and suggest that subgroups of patients with enhanced tumor angiogenesis seem to have an unfavorable profile, while signaling through VEGF receptors in cancer cells can promote events associated with tumor progression. Existing evidence suggests that HER2 activation is one of the several mechanisms that promote angiogenesis and that HER2-amplified breast cancers have increased angiogenesis[ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, conducted in the pre-trastuzumab era, we found that high VEGF-A, VEGF-C, VEGFR2 and VEGFR3 protein expression was associated with certain adverse prognostic factors, such as ER/PgR-negative and/or HER2-positive status, suggesting that high protein expression of VEGF family members might have a negative prognostic impact on DFS or OS. Our findings are consistent with the results of recent studies[ 19 , 29 , 30 ] and suggest that subgroups of patients with enhanced tumor angiogenesis seem to have an unfavorable profile, while signaling through VEGF receptors in cancer cells can promote events associated with tumor progression. Existing evidence suggests that HER2 activation is one of the several mechanisms that promote angiogenesis and that HER2-amplified breast cancers have increased angiogenesis[ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The issue of whether angiogenesis is enhanced in distinct breast cancer subtypes has been discussed in the literature[ 29 , 30 , 34 36 ]. Gene expression profiling has been used to classify breast carcinomas into molecular subtypes with significant differences in incidence, risk factors, prognosis and treatment sensitivity[ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although high intratumor VEGFA levels detected by immunohistochemistry have been linked to poor breast cancer outcome, most studies have been small and results controversial. 96 , 97 Our analysis showed breast cancers in the highest quartile of VEGFA expression fare worse than all others, and the prognostic value of high VEGFA levels is increased by sequential addition of high SOX2, SNAI2 and decreased GABRE (a surrogate for miR-452) expression. This finding is less important for its prognostic significance than it is as a confirmation of the molecular pathway identified herein.…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, membranous and nuclear NHERF1 reconfirmed their defensive role, being negatively related to cVEGF expression. VEGF is well known as the principal modulator in the process of cancer growth, invasion and metastasis, through new microvessel formation and lymphovascular invasion [ 33 ]. Previous studies carried out by our équipe had already reported a NHERF1/VEGFR1 relationship with poor clinical outcome in invasive BCs, indicating a possible interaction between the two proteins [ 19 ].…”
Section: Discussionmentioning
confidence: 99%